2021 Comprehensive Surveillance Review : Background Paper on Traction. (Policy Papers; Policy Paper, 2021)
This paper presents traction as a multidimensional concept and discusses a comprehensive and complementary set of approaches to attempt to measure it based on the Fund's value added to policy dialogue and formulation and public debate in member countries.